2016
DOI: 10.1007/s10529-016-2199-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparation of the effects of different 5′-untranslated regions (UTRs) on gene expression in HEK293 cells

Abstract: Different UTRs can significantly affect protein expression. Additionally, the findings also will be useful in biological applications that require tuning of gene expression and system optimization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Both rs2803495 and rs2803496 variants are in the 5′-untranslated region (UTR) of TREML4 . The 5′-UTR contains regulatory regions, such as selenocysteine insertion sequence elements, AU-rich elements, riboswitches, and microRNA-binding sites that affect translational efficiency, subcellular localization, and mRNA stability 22 . Therefore, the 5′-UTR plays an important role in controlling gene expression 23 , and polymorphisms in this region may influence mRNA stability and, consequently, gene expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…Both rs2803495 and rs2803496 variants are in the 5′-untranslated region (UTR) of TREML4 . The 5′-UTR contains regulatory regions, such as selenocysteine insertion sequence elements, AU-rich elements, riboswitches, and microRNA-binding sites that affect translational efficiency, subcellular localization, and mRNA stability 22 . Therefore, the 5′-UTR plays an important role in controlling gene expression 23 , and polymorphisms in this region may influence mRNA stability and, consequently, gene expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…4C, and 4D). Interestingly, hybrid intron and EF-1α intron A, which were originally reported to have the function of upregulating gene expression (Melcher, Grosch et al 2002, Zhang, Zha et al 2016), instead of working as expected, showed signi cant inhibition of eGFP gene expression in L929 and MARC145 cells after combination with the CMV enhancer and EF-1α core promoter.…”
Section: Resultsmentioning
confidence: 73%
“…In addition, introns can also improve the translation e ciency of mRNA (Shaul 2017). It is commonly believed that UTR is primarily responsible for regulating the expression levels of post-transcriptional genes by altering the stability of mRNA, translation e ciency and subcellular localization, and it has been found that the 5 '-UTR of mRNA affects the expression of prokaryotes and eukaryotes at the translational level mainly by forming secondary structures (Crook, Freeman et al 2011, Zhang, Zha et al 2016. For the 3'UTR and terminator, studies of prokaryotic expression systems have found that both terminator and engineered 3'UTR elements can drastically alter the level of heterologous expression (Cambray, Guimaraes et al 2013).…”
Section: Optimization Of Expression Vectors Is the Main Means To Impr...mentioning
confidence: 99%
“…The two significant SNPs divided the 77 lines into two major haplotypes (Hap1: AA; Hap2: CC), a t -test showed that the BSH-LTC (1.178) of Hap1 was significantly (p< 0.05) lower than that (1.417) of Hap 2 ( Figure 3B ). In contrast to synonymous variants and intron_variants, those in the 5’ UTR tend to cause changes in gene transcriptional levels and thus lead to phenotypic variations ( Bashirullah et al., 2001 ; Zhang et al., 2016b ). We then detected the expression of ZmbZIP107 in the two contrasting haplotypes under Pb treatment by using RT-qPCR.…”
Section: Resultsmentioning
confidence: 99%